Perovskite Thin Film Solar Cells Based on Inorganic Hole Conducting Materials - Pan-Pan Zhang; Zheng-Ji Zhou; Dong-Xing Kou; Si-Xin Wu (International Journal of Photoenergy)
Organic-inorganic metal halide perovskites have recently shown great potential for application, due to their advantages of low-cost, excellent photoelectric properties and high power conversion efficiency. Perovskite-based thin film solar cells have achieved a power conversion efficiency (PCE) of up to 20%. Hole transport materials (HTMs) are one of the most important components of perovskite solar cells (PSCs), having functions of optimizing interface, adjusting the energy match, and helping to obtain higher PCE. Inorganic p-type semiconductors are alternative HTMs due to their chemical stability, higher mobility, high transparency in the visible region, and applicable valence band (VB) energy level. This review analyzed the advantages, disadvantages, and development prospects of several popular inorganic HTMs in PSCs.